2018
DOI: 10.1016/j.lungcan.2018.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Minute ventilation-to-carbon dioxide slope is associated with postoperative survival after anatomical lung resection

Abstract: Objectives:The aim of the study was to identify whether ventilation-to-carbon dioxide output (VE/V CO2) slope obtained from cardiopulmonary exercise test (CPET) as part of the preoperative functional workup was an independent prognostic factor for short and long-term survival after major lung resection. Patients and Methods: 974 consecutive patients undergoing lobectomy (n=887) or segmentectomy (n=87) between April 2014 to March 2018 were included. 209 (22%) underwent CPET, and pulmonary function tests and sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 18 publications
1
22
1
1
Order By: Relevance
“…First, in contrast to V E /VCO previous studies found V E /VCO 2 slope to be a strong predictor of PPC [5][6][7][8] and its inclusion in risk stratification algorithms of lung resection candidates has been suggested, 20 though not yet adopted. Results of our large, prospective, multicenter study support inclusion of V E /VCO 2 slope within functional evaluation algorithms of lung resection candidates.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…First, in contrast to V E /VCO previous studies found V E /VCO 2 slope to be a strong predictor of PPC [5][6][7][8] and its inclusion in risk stratification algorithms of lung resection candidates has been suggested, 20 though not yet adopted. Results of our large, prospective, multicenter study support inclusion of V E /VCO 2 slope within functional evaluation algorithms of lung resection candidates.…”
Section: Resultsmentioning
confidence: 96%
“…1,2 However, several studies have shown ventilatory efficiency, defined as the slope of ratio of minute ventilation to carbon dioxide production (V E /VCO 2 ), to be a better predictor of postoperative pulmonary complications (PPC) 5,6 and mortality. 7,8 By the alveolar gas equation, V E /VCO 2 is inversely related to ventilatory drive and positively to dead space ventilation. 9 Partial pressure of end-tidal carbon dioxide (P ET CO 2 ) shares these same physiologic determinants with V E /VCO 2 10 and may be easily measured at rest, suggesting that P ET CO 2 may be an alternative to V E /VCO 2 for those patients who are not able or do not want to exercise.…”
mentioning
confidence: 99%
“…For instance, TORCHIO et al [69] reported that a high V′ E -V′ CO 2 slope was the strongest predictor of mortality after pneumonectomies, a finding extended by MIYAZAKI et al [70] to less extensive anatomical lung resections. ELLENBERGER et al [71] found that a particularly high V′ E /V′ CO 2 (>40) predicted poor survival after radical surgery for lung cancer.…”
Section: Impact Of Copd Comorbidities On V′ E /V′ Comentioning
confidence: 89%
“…In this case, the patient's exercise capacity, as reflected by the peak VO 2 was reassuringly normal. The VE/CO 2 slope was also suggestive of a low perioperative risk [9,[12], [13], [14]]. Given the patient's history of severe COPD, previous lung resection surgery, and severe derangements in differential lung perfusion and ventilation testing, this intraoperative oxygen challenge test was an effective intervention to definitely assess safety and tolerance of single lung function under general anaesthesia and provide an informed decision for the patient about the appropriate therapeutic options.…”
Section: Discussionmentioning
confidence: 99%
“…1). However peak oxygen consumption was reassuringly normal measured at 16.7 ml/min/kg and the nadir minute ventilation/carbon dioxide (VE/VCO 2 ) slope was of 24 implying a limited risk of perioperative cardiovascular morbidity [10,[12], [13], [14], [15]]. The estimated anaerobic threshold was 10.9 ml/kg/min.…”
Section: Presentation Of Casementioning
confidence: 99%